Tingkat Pemanfaatan Bahan Koleksi sebagai Pemenuhan Kebutuhan Informasi pada Anak di Rumah Literasi Ranggi Sumatera Utara - Yusniah Yusniah; Putri Lestari; Ineke Mayliningrum (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Reading books for children is very important for a child's growth and development, especially when entering a formal educational environment such as elementary school. This activity aims to explore the benefits of having a literacy house, especially to improve children's learning abilities. Using participatory rural appraisal methods or techniques and data collection techniques through interviews, observation, focus group discussions and literature review. The results of the study show that the Ranggi Literacy House at the PWI Complex, Percut Sei Tuan, Deli Serdang acts as a source of learning for children, especially underprivileged children, a place for character formation, and a source of information for parents. in child care, community recreation and training facilities, even facilities for mothers to express their talents. The results of the study indicate that the availability of children's literature in the mother and child library services is quite adequate. Judging from the suitability of literature for the age level and information needs of children, it is in accordance with the availability of 3D collections for children who cannot read, and the availability of fairy tales, comics, religious books, history books, and other textbooks. The use of children's literature at the Ranggi Literacy House is quite good. This is shown by the enthusiasm of users in reading literature and utilizing the available facilities. Obstacles faced by the Ranggi Literacy House in improving the reading culture of its users: they do not yet have an audio-visual collection, even though audio-visual collections can contribute to improving children's reading culture because in reality children tend to prefer using technology and prefer to see and hear. However, in fulfillment of this, the Ranggi Literacy House also often holds watching folklore or other stories together as a form of character education for children. Keywords: Reading garden, learning resources, educational-recreational information sources.